The implementation of constructivist modules to correct misconceptions on the human reproductive system concept. (February 2020) - Ramadhani, R; Abdullah, A; Hasanuddin, H; Khairil, K; Muhibbuddin
Abstract: It is necessary to find appropriate learning solutions to solve students' misconceptions on the human reproductive system concepts. This study aims to determine whether learning through the implementation of a constructivist module influences the reconstruction of students' knowledge about the human reproductive system. The method used in this study was experimental with one group pre-test and post-test design. The population consisted of 272 students from science class XI of SMAN 10 Fajar Harapan Banda Aceh and SMAN Modal Bangsa Aceh Province. A total of 107 students were chosen by random sampling. The study was carried out over four months from March to July 2019. The supporting instruments used were the learning media and the data collection instruments in the form of multiple-choice test questions with Certainty of Response Index (CRI). The data collected through a pre-and post-test were analyzed using percentages. The results show that the number of students who understand certain concepts rose by 52.36%, the number of students who had misunderstandings decreased by 43.58%, and the number of students who had misconceptions fell by 9.94%. So, it is concluded that learning through the constructivist module is effective in improving concept reconstruction and students' learning outcomes.